CHRONIC EFFECTS OF PULSED ELECTROMAGNETIC FIELD (PEMF) APPLICATION ON HEMODYNAMIC AND CARDIOVASCULAR PHYSIOLOGICAL VARIABLES (CIPEEX, 2025)
Objectives: To determine the effects of 8 treatment sessions inducing contractions by pulsed electromagnetic field (PEMF) on systolic blood pressure (SBP), diastolic blood pressure (DBP), HR, as well as on the visual analog scale (VAS). Methods: 23 participants older than 65 years and of both sexes participated in the study. Participants were invited to perform 8 sessions of PEMF intervention (2x/week), through electromagnetic pulse-induced contraction on both thighs and legs. 30 min were administered per session. Before and after the intervention, hemodynamic and cardiovascular analysis were performed, as well as the response to the VAS scale. Results: SBP and DBP did not demonstrate significant differences pre and post PEMF intervention sessions (SBP: p = 0.982; DBP: p = 0.791), as well as HR (p = 0.970). The Friedman test demonstrated significant differences between the PEMF intervention sessions for VAS (p = 0.001). Conclusion: PEMF treatment in the elderly was effective for modifying pain levels. However, the number of sessions was not sufficient to produce significant adaptations regarding hemodynamic variables.
Keywords: hemodynamics; aging; health